The Impact of Diaspora Remittances on Economic Growth in Zimbabwe (2015–2024) - Nyoka, Charles (Acta Universitatis Danubius. Œconomica, 2025)
Zimbabwe went through many economic phases since it attained independence in 1980. The country was starved of foreign currency inflows which provide capital for productive sectors to attain economic development. As her foreign currency earning capacity from exports had collapsed, she turned to the inflows from Zimbabweans in the diaspora for survival. This paper determines whether diaspora remittances had a positive effect on Zimbabwe’s economic growth from 2015–2024 using descriptive analysis, correlation analysis, and multiple linear regression analysis. The findings affirm that remittance inflows play a crucial role in supporting GDP growth. Descriptive statistics show significant macroeconomic volatility. Trend analysis confirms a divergence between volatile GDP growth and steady remittance inflows, highlighting the counter-cyclical role of remittances. Correlation analysis supports this, showing a strong positive link between remittances and GDP growth. Multiple regression analysis shows that log-transformed remittances significantly impact GDP growth. This emphasizes the substantial growth-promoting potential of remittances, likely via channels such as household consumption and investment. Overall, remittances are crucial for inclusive growth in Zimbabwe’s macroeconomic policy and hence future fiscal and monetary plans should incorporate this insight by promoting formal remittance channels, increasing diaspora engagement, and maintaining macroeconomic stability to maximize their developmental benefits.